‘A Social Constructivist Approach to translator Education: Empowerment from Theory to Practice’, de Don Kiraly (Gragoatá, 2016)
Livro resenhado:KIRALY, Don. A social constructivist approach to translator education: empowerment from theory to practice. Manchester, UK: St. Jerome Publishing, 2000. 207 p.